SYSTEM SPECIFIC CHARACTERISTICS OF GENERAL SECONDARY EDUCATION PROCESSES (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article provides information on independent education, self-education, independent work, as well as system-specific features of education and training processes, which are organized by students themselves in general secondary education schools